Constructive feminism : women's spaces and women's rights in the American city - Spain, Daphne (Ithaca : Cornell University Press, 2016)
This book examines the deliberate and unintended spatial consequences of feminism's second wave, a social movement dedicated to reconfiguring power relations between women and men. Placing the women's movement of the 1970s in the context of other social movements that have changed the use of urban space, this book argues that reform feminists used the legal system to end the mandatory segregation of women and men in public institutions, while radical activists created small-scale places that gave women the confidence to claim their rights to the public sphere.
Introduction : spatial implications of the second wave -- Feminist practice : social movements and urban space -- Women's centers : nurturing autonomy -- Feminist bookstores : building identity -- Feminist health clinics : promoting reproductive rights -- Domestic violence shelters : protecting bodily integrity -- After the second wave : necessary spaces.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed April 5, 2016).
JSTOR
Keywords: Feminism -- United States -- History -- 20th century; Women's rights -- United States -- History -- 20th century; Public spaces -- United States -- History -- 20th century; Urban women -- United States -- History -- 20th century; Women and city planning -- United States -- History -- 20th century; Feminism and architecture -- United States; Feminist geography -- United States; Féminisme -- États-Unis -- Histoire -- 20e siècle.; Espaces publics -- États-Unis -- Histoire -- 20e siècle.; Femmes en milieu urbain -- États-Unis -- Histoire -- 20e siècle.; Femmes et urbanisme -- États-Unis -- Histoire -- 20e siècle.; Féminisme et architecture -- États-Unis.; Géographie féministe -- États-Unis.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; SOCIAL SCIENCE -- Women's Studies; Feminism; Feminism and architecture; Feminist geography; Public spaces; Urban women; Women and city planning; Women's rights; United States; Féminisme -- États-Unis -- Histoire -- 20e siècle.; Droits des femmes -- États-Unis -- Histoire -- 20e siècle.; Espaces publics -- États-Unis -- Histoire -- 20e siècle.; Femmes et urbanisme -- États-Unis -- Histoire -- 20e siècle.; 1900-1999; Electronic books; History